Um estudo sobre as articulações entre história da Matemática e ensino de Trigonometria: análise de teses e dissertações - Souza, Adriana Celia Lopes de (2020)
This dissertation aims to investigate the different approaches taken by academic studies that sought to integrate the history of mathematics in the teaching and learning of trigonometry. To this end, we examined dissertations in the period between 2008 and 2017. We used Bardin's Content Analysis (1977) to examine these works and separated them into three focuses according each one’s theme: a) learning, b) teacher training and c) teaching. These works state that the history of mathematics is an interesting resource that can be used for the elaboration of didactic and pedagogical activities, but the approaches given to the uses of history to promote learning, teacher training and the teaching of trigonometry did not seem to us to be consensual. We used Saito (2013, 2015, 2016 and 2018), Miguel and Miorim (2005), Miguel and Brito (1996), Mendes (2010), Fried (2001), amongst others, as theoretical background in order to support our research with concepts, definitions, and arguments or aspects that make the work presented here relevant. The various reflections present in theoretical framework texts about the manner in which historical discourse is presented in academic productions are a relevant contribution to research, as we can find possible answers to our research problem from them. As diversas reflexões presentes nos textos do arcabouço teórico sobre o modo como se apresenta o discurso histórico nas produções acadêmicas são uma relevante contribuição para a pesquisa, uma vez que, a partir delas, podemos encontrar respostas possíveis para a nossa problemática da pesquisa